Excessive running induces cartilage degeneration in knee joints and alters gait of rats - Jeffrey M. Beckett; Jin Wu; M. Schultz; Andrew Chen; D.L. Tolbert; Berton R. Moed; Zijun Zhang (2012)
Abstract The goal of this study was to develop an aggressive running regimen for modeling osteoarthritis (OA) in rats. Twelve Wistar rats were randomly placed into either a running group or a non‐running group to serve as the control. The running rats used a motorized treadmill to run either 30 km in 3 weeks or 55 km in 6 weeks. Each week, the prints of hind paws were obtained when rats were made to walk through a tunnel. The resulting prints were digitalized for analyses of stride length and step angle. The histology of the knees was examined at 3 and 6 weeks and the OA pathology in the knees was quantified by Mankin's score. Osteoarthritic pathology developed in the knees of the running rats, including decreased proteoglycan content, uneven type II collagen distribution in the cartilage matrix, increased MMP‐13 expression, expanded calcified cartilage zone, and clefts and defects in articular cartilage. The pathology worsened from running for 3 to 6 weeks. Gait analysis revealed an inverse correlation between paw angle and the grades of OA pathology. In conclusion, excessive running induces joint degeneration and a unique gait pattern in rats. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 30:1604–1610, 2012